A simplified sustainable manufacturing paradigm for small scale gold production systems. - Soriano, Virginia Jose
The Philippine gold industry has contributed largely to the country's economy by generating and supporting thousands of small scale industries in mining, processing and jewelry manufacturing. However, small-scale gold production in the country is described as an informal industry with minimal standards, thus affecting their competitiveness and sustainability. This study aims at using a simplified paradigm that integrates the economic, environment, technology, legal and social aspects for sustainability in gold manufacturing. The study used life cycle thinking and systems approach to assess the impact of current practices on the said aspects of the small scale gold production activities. The assessment results showed the important sources of environmental burden, inefficiency, technological and social impacts. Further, through literature review and interviews of industry stakeholders, the identified issues and concerns include the availability of channels to assess miner's information, trainings, technology and programs for cleaner and more efficient production, as well as clear and specific environmental legislation and regulations. Finally, the study identified opportunities that could potentially improve and balance sustainability goals of the small scale gold manufacturing industries.
Keywords: Life Cycle; Small scale gold production; Sustainability